PERBANDINGAN KADAR HORMON T4 (TIROKSIN) PADA CAIRAN FOLIKEL OVARIUM DENGAN SERUM SAPI - , RIYANDINI PUTRI; , Dr. drh. Rr. Amelia Hana, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The increasing gap between the demands for domestic beef production requires maximum effort to increase the productivity of beef cattle in various agro-ecosystems in Indonesia. Productive female cattle are cows that need to always be in sound condition and good to produce good offspring. Therefore, the reproductive status is expected to be in maximum condition. The study was conducted using the 5 cows from Giwangan Slaughter House, Yogyakarta. Serum and follicular fluid samples taken from the same cow. Serum samples were obtained from blood and follicular fluid was then tested by using ELISA to determine the amount of T4. ELISA results were statistically analyzed using the Independent T-test method with the help of SPSS computing program. T4 level in serum, the highest was 30,37 Î¼g/dL while the lowest was 15,80 Î¼g/dL with an average of 22,35 Î¼g/dL. T4 level in follicular fluid, the highest was of 20,40 Î¼g/dL, while the lowest was 9,60 Î¼g/dL with an average of 14,70 Î¼g/dL. Average level of T4 in follicular fluid is lower than serum. Variations in the concentration of T4 intergonad apparently due to some differences in the permeability of the blood-ovary barrier to T4 and the relative concentration of total protein (TP) in the follicular fluid. From the study, it was concluded that the concentration of T4 in follicular fluid has the same range as in bovine serum. Keywords: thyroxine, follicular fluid, serum, slaughter house